Histological Grading of Oral Cancer: A Comparison of Different Systems and Their Relation to Lymph Node Metastasis - Doshi , Neena P; Shah , Siddharth A; Patel , Keyuri B; Jhabuawala , Munira F (National Journal of Community Medicine, 2011)
Oral squamous cell carcinoma has a great predisposition to produce metastasis in lymph nodes. In clinical practice, the treatment plan and prognosis of oral squamous cell carcinoma is mainly based on the primary tumor, regional lymph node metastasis, and distant metastasis (TNM) staging system. However, this system does not provide any information on the biological characteristics and thus an aggressive clinical behavior of the tumor. The aim of this study was to assess some indicative histological parameters that would assist in the prognosis of these lesions. All cases of oral squamous cell carcinoma's treated with wide excision of growth with radical neck dissection, registered between 2006 – 2009 in the Department of Pathology, Shree Krishna Hospital, Karamsad were studied retrospectively. Surgical specimens of 31 metastasizing tumors were compared with 26 tumors which did not metastasize. Each case was graded according to: Broders' classification in the whole thickness of tumor, Anneroth’s multifactorial grading system and Bryne’s deep invasive cell grading system. Bryne’s score showed an Odds ratio of 2.12, 95% C.I. (1.41, 3.18). The predictive value of the score is 73.7%. Bryne’s deep invasive cell score showed significant relation with lymph node metastasis. Other grading methods failed to show any relation with metastasis. Bryne’s deep invasive cell grading system in appropriate biopsy specimens would be of great value in predicting lymph node metastasis and treatment results of oral squamous cell carcinoma.